2019
DOI: 10.17135/jdhs.2019.19.4.288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bamboo Salt with Sodium Fluoride on the Prevention of Dental Caries

Abstract: Background: Dental caries is one of several prevalent oral diseases caused by dental plaque biofilms. This study evaluated the anti-cariogenic effects of a bamboo salt (BS) and sodium fluoride (NaF) mixture on oral bacteria. Methods: The effects of several mixtures of NaF and BS on acid production, growth, and adhesion to glass beads of Streptococcus mutans, and their anti-cariogenic properties were investigated. The growth of S. mutans was measured according to optical density at 3, 6, 9, 12, 15, 18, and 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Various properties attributed to the cariogenesis of this microorganism including its growth, acid production, adherence to glass beads, and expression of gtfB, gtfC, gtfD, and ftf genes were signi cantly restrained by the Bamboo salt and sodium uoride mixture. It was concluded that Bamboo salt and sodium uoride can synergically act in inhibiting the cariogenic potential of Streptococcus mutans [15], which is in line with the results of the present in-vivo study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Various properties attributed to the cariogenesis of this microorganism including its growth, acid production, adherence to glass beads, and expression of gtfB, gtfC, gtfD, and ftf genes were signi cantly restrained by the Bamboo salt and sodium uoride mixture. It was concluded that Bamboo salt and sodium uoride can synergically act in inhibiting the cariogenic potential of Streptococcus mutans [15], which is in line with the results of the present in-vivo study.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the antimicrobial e cacy of Bamboo salt toothpaste, a recent in-vitro study by Lee et al (2019) investigated the e cacy of Bamboo salt combined with sodium uoride on streptococcus mutans. Various properties attributed to the cariogenesis of this microorganism including its growth, acid production, adherence to glass beads, and expression of gtfB, gtfC, gtfD, and ftf genes were signi cantly restrained by the Bamboo salt and sodium uoride mixture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, Bamboo salt is made by packing sea salt in bamboo tubes, plugging the ends with mud, and baking it on pine firewood. This method results in higher mineral content of calcium, potassium, copper, and zinc ions in Bamboo salt compared to sun-dried salts while maintaining its main ingredient, i.e., sodium chloride [20,21]. Mineral-rich Bamboo salt is highly alkaline (pH = 11.4), making for its potent antioxidant action [22].…”
Section: Introductionmentioning
confidence: 99%